Off-resonant RF heating of strongly magnetized electrons in ultracold neutral plasma - Guthrie, John M., author; Roberts, Jacob, advisor; Fairbank, William, Jr., committee member; Gelfand, Martin, committee member; Wilson, Jesse, committee member (Colorado State University. Libraries, 2021)
Magnetic fields are common in many plasma systems. Ultracold neutral plasmas (UCPs) are capable of not only accessing strong Coulomb coupling physics but also strong and extreme electron magnetization regimes, as well. These magnetization regimes, as defined by Baalrud and Daligault [S. Baalrud and J. Daligault, Phys. Rev. E, 96, 043202 (2017)], are predicted to modify screening or binary collision properties as the electron cyclotron radius approaches or subceeds the relevant plasma length scales. UCPs provide an advantageous testing ground for measuring magnetized electron-ion interactions, such as collisional heating induced by applied off-resonant RF fields. The experiments described in this thesis are focused on observations of RF heating in a UCP made from a photoionized cloud of ultracold 85Rb at three electron magnetization strengths that span the weakly-strongly magnetized boundary to the strongly-extremely magnetized boundary. Relative comparisons between heating rates at different magnetic fields were measured with ~20% precision, and an absolute determination of the heating rate near the weak-strong magnetization boundary is determined with ~40% precision. The results from these experiments were compared to theoretical predictions we developed that account for the finite-RF amplitude conditions used in the UCP measurements. This finite-amplitude heating rate theory is shown to be an extension of low-amplitude magnetized AC conductivity treatments as well as unmagnetized nonlinear collisional radiation absorption treatments. Mixed agreement was discovered between our observations and the theory for the three magnetic fields investigated: 10.6, 65, and 134 G. The measured absolute RF heating rate at 10.6 G and the relative rate between 134 and 10.6 G are in agreement with predictions within uncertainty; the relative rate between 65 and 10.6 G was observed to be a factor of ~3 lower than the predictions, with an absolute difference---in terms of the measurement uncertainty---on the order of 10σ. The implications of this disagreement are discussed, and future measurements that can be conducted with this technique are presented.
Keywords: cyclotron motion; plasma heating; ultracold plasma; electron-ion collisions; Bremsstrahlung; stopping power